"Everybody needs everyone": a case study of workplace learning after a downsize. Issue 2 (16th October 2019) - Miller, Sarah M.; Kim, JungHwan; Lim, Doo Hun
Abstract : Purpose: This study aims to explore how employees' emotions after downsizing impact their learning that they partook in after the downsizing event. Design/methodology/approach: The methodological approach was a qualitative case study. Nine employees, considered layoff survivors in a downsized organization, participated in semi-structured interviews. For data analysis, authors performed an initial, focused and axial coding. Findings: The findings highlight three themes: "resilience, " "loyalty" and "moral support." These themes show the empathy that layoff survivors experienced and the impact the layoff had on their commitment to the organization, as well as the social learning that occurred after downsizing. Practical implications: Downsized organizations need to consider the emotions of employees who survive layoffs and how layoffs impact their behavior at work, particularly their learning behavior. Organizations need to understand how to positively impact layoff survivors' emotions to influence the survivors' willingness to learn and implement the changes within the organization. Providing outlets for survivors to network within the company, as well as meaningful opportunities, is one of the few ways of addressing employees' emotions and ensuring they will be encouraged to change with the organization. Originality/value: Research that explores how emotions resulting from an organizational downsize impact employees' learning is minimal. Although much of the downsizing research does explore layoff survivors' experiences after a downsizing, it does not address the emotional factors or the learning experiences. This study seeks to fill this gap.